EXPLANATORY GAP AND HARD PROBLEM OF CONSCIOUSNESS ON PHILOSOPHY OF MIND: A CRITICAL STUDY ON SOUL-BODY RELATION POINT OF VIEW IN MULLÃ‚ ÅšADRÃ‚â€™S PHILOSOPHY - Toresano, Wa Ode Zainab Zilullah; al-Walid, Kholid (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2023)
AbstractÂ The goal pf this research to examine ÅšadrÃ¢â€™s view on the â€œsoul-body relationâ€ in order to solve the â€œexplanatory gap and the hard problem of consciousnessâ€ which are the basic core of the mind-body problem in the philosophy of mind. The explanatory gap explains how physical property can give influence non-physical things conversely. Meanwhile, the hard problem mentions how physical system (material) can produce subjectivity in the mind (non-physics/ immaterial), especially when we have experience. In this context, there is a gap that appears between the immaterial mind and the material body.Â According to the authorâ€™s view, ÅšadrÃ¢â€™s philosophy of mind-body relation can solve the problem because it is based on principles of Hikmah Mutaâ€™Ã¢liyah philosophy, which is â€œmonis of existential-dualism of essentialâ€ [in authorâ€™s term]. In this research, the author develops the research using Paul Ricoeurâ€™s hermeneutic and philosophical approaches.Â This research would like to highlight Hikmah Mutaâ€™Ã¢liyah philosophy, which synthesizes philosophy, theology, and tasawuf (â€˜irfÃ¢n), which can be the reference for Muslims (or anyone interested in Islamic Philosophy) to solve philosophical problems. In other explanations, Islamic tradition [in this paper it is represented by ÅšadrÃ¢] can contribute to contemporary philosophical discourse without making tendentious claim that Western Philosophy cannot solve problems better than the philosophy of ÅšadrÃ¢.